The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1519-6984.18415
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of nitrogenous compounds on survival and growth of juvenile pink shrimp

Abstract: In response to growing worldwide market demand, intensive shrimp farming, based on high feed, has developed over the past decade. The nitrogenous compounds mainly generated by animal excretion can cause deterioration of water quality and produce chronic or even acute toxicity to aquatic animals. As prevention, theoretical safety levels have been estimated from acute toxicity tests and they are traditionally used to prevent toxic effects on biota. However, are those concentrations of nitrogenous compounds reall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…For example, in the tanks with Penaeus vannamei, which contained up to 10 individuals of 10.7 g average weight, receiving 6.2 g of food per day, it was observed pH decrease if compared with the fasting treatment water completely clear (in the absence of food and almost also of wastes), where pH was significantly more alkaline (8.06), although within the normal range for cultivation. Nitrite reached 0.56 mg L -1 N-NO2in the mixed fasting treatment, but this concentration is much lower than what considered unsafe for the cultivation of another species of penaeid, F. paulensis, of 2.55 mg L -1 NO2 - (Wasielesky et al, 2017). However, the fact that this treatment lasted much less time (38 days to the harvest of the last tank) than the other five treatments (60 days), evidently also affected this comparison.…”
Section: Discussionmentioning
confidence: 76%
“…For example, in the tanks with Penaeus vannamei, which contained up to 10 individuals of 10.7 g average weight, receiving 6.2 g of food per day, it was observed pH decrease if compared with the fasting treatment water completely clear (in the absence of food and almost also of wastes), where pH was significantly more alkaline (8.06), although within the normal range for cultivation. Nitrite reached 0.56 mg L -1 N-NO2in the mixed fasting treatment, but this concentration is much lower than what considered unsafe for the cultivation of another species of penaeid, F. paulensis, of 2.55 mg L -1 NO2 - (Wasielesky et al, 2017). However, the fact that this treatment lasted much less time (38 days to the harvest of the last tank) than the other five treatments (60 days), evidently also affected this comparison.…”
Section: Discussionmentioning
confidence: 76%
“…Through the improvement of aquaculture techniques, cultivation conditions have intensified by increasing the production of this crustacean. However, one of the limiting factors for their production is the generation and accumulation of nitrogenous residues, mainly ammonia, originated from animal excretion, degradation of food residues and decomposition of organic debris in culture systems (Jia et al, 2015;Romano & Zeng, 2013;Wasielesky, Poersch, Martins, & Miranda-Filho, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of ammonia tend to accumulate in body fluids of aquatic organisms, including shrimp (Liang et al, 2016), causing sublethal or lethal toxic effects. Among these, osmoregulatory disorders (Romano & Zeng, 2013), increased oxygen consumption (Barbieri, 2010), decreased growth rates and increased mortality (Campos, Furtado, D'incao, Poersch, & Wasielesky, 2015;Wasielesky et al, 2017), Krebs cycle suppression and decoupling of oxidative phosphorylation (Ding et al, 2017), changes and histological lesions (Dutra et al, 2017), decreased antioxidant capacity and oxidative stress (Jia et al, 2015) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, nitrite causes a decrease in the oxygen affinity of the shrimp hemolymph, eliminating its normal oxygen carrying capacity, and eventually resulting in asphyxiation (Jiann-Chu and . Indeed, it has been reported that nitrite has serious deleterious effects on shrimp growth (Wasielesky et al, 2017), immunity (Tseng and Chen, 2004), and survival (Wasielesky et al, 2017;Valencia-Castaneda et al, 2018. Therefore, low aquatic nitrite concentrations must be maintained for successful shrimp farming.…”
Section: Introductionmentioning
confidence: 99%